Power system capacity expansion planning model considering carbon emissions constraints - Giraldo, Diego Adolfo Mejía; Lezama, Jesús María López; Pareja, Luis Alfonso Gallego [UNESP] (My University, 2012)
This paper presents a power system capacity expansion planning modelconsidering carbon emissions constraints. In addition to the traditionaltechnical and economical issues usually considered in the planning process, two environmental policies that consist on the taxation and the annual limitsof carbon dioxide (CO 2) emissions are considered. Furthermore, the gradualretirement of old inefficient generation plants has been included. The approachguarantees a cleaner electricity production in the expanded power system ata relatively low cost. The proposed model considers the transmission systemand is applied to a 4-region and 11-region power systems over a 20-yearplanning horizon. Results show practical investment decisions in terms of sustainability and costs.
Keywords: Capacity expansion planning; Capacity factor; Carbon dioxide emissions; Sustainability